Factors Affecting Ground Ice Melting - Mills, Peter F. (My University, 1973)
The thaw rates of the active layer above the permafrost zone from a series of sites along the Hudson Bay coastline at lat. 56° have been examined with respect to temperature and moisture gradients, the characteristics of the surface layer and the bulk thermal properties for each profile. The thermal properties have been examined using firstly a Fourier approach with the parameter of degree days and using secondly a graphical approach employing thermal relationships obtained in the laboratory analyses by Kersten (1949).
It was found that thaw rates are controlled by the interaction of a number of environmental factors of which vegetation appears to be the most important.
The two approaches to the derivation of thermal properties give quite different results, such that the graphical approach is deemed to be unsuitable to field application.
Keywords: factors, ground ice, melting, temperature, moisture gradients, thermal, environmental